Post-cold war Turkish-Russian relations: the limits of competition and cooperation in Eurasia - Kelkitli, Fatma Aslı. (Thesis (Ph.D.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2012., 2012)
This dissertation examines post-Cold War Turkish-Russian relations in their political, economic and military aspects. The study, first of all, aims to shed light on the current nature and motives of the relationship, whether it is an example of genuine rapprochement based on common determination and willingness on both sides or a conjectural coupling which drew two states closer due to their discomfort and disappointment with some policies of other actors such as the EU and the USA. Secondly, the dissertation intends to find out to what extent the growing economic relations, especially Turkey’s energy dependence on Russia, contributes to the easing out of political tensions between the two countries. Lastly, the study explores whether the growing economic cooperation and intensifying political dialogue between Turkey and Russia can bring out common outlook and joint policy actions toward the resolution of the regional conflicts in the South Caucasus. The research based on an analysis of documents concerning the topic along with the in-depth interviews I have conducted with the representatives of the Turkish-Russian business associations and officials in the Turkish Ministry of Foreign Affairs demonstrates that Turkey and Russia have been engaged in a deliberate compromise which is strengthened by their ascending economic relations particularly by the increasing and diversifying collaboration in the energy field. However, consolidated economic ties and increasing contacts at the governmental as well as at business and people-to-people levels are not adequate to prevail over the competition and political divergence regarding Nagorno Karabakh, South Ossetia and Abkhazia issues in the South Caucasus.
Keywords: Eurasia -- Economic conditions.